DEVELOPMENT OF TEACHING MATERIALS FOR "ENGLISH AND ARABIC FOR EDUCATIONAL OF NATURAL SCIENCE AT THE STATE COLLEGE ISLAMIC OF MANDAILING NATAL - Saputra, Muhammad Ari; Linur, Rahmat; Supriani, Ria Rafita (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
This research employs a development method with a Research and Development (R&D) approach. The objective of this study is to develop a textbook for "English and Arabic for Educational of Natural Science" for the Educational of Natural Science Program at the State college Islamic of Mandailing Natal (STAIN Mandailing Natal). The results of this research will be utilized by English and Arabic lecturers teaching in this program. The research applies the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The strength of this development model lies in its systematic and comprehensive implementation process, an aspect not found in other models. Specifically, Branch (2009:17) categorizes these stages into five: Analysis, Design, Development, Implementation, and Evaluation. The outcome of this research is the "English and Arabic for Educational of Natural Science" textbook at STAIN Mandailing Natal, which includes various important themes designed to enhance students' abilities to use English and Arabic in the context of natural sciences. The content of this textbook includes topics such as meeting people, parts of the body, health, plants, animals, environment, and education. The "English and Arabic for Educational of Natural Science" textbook at STAIN Mandailing Natal not only serves as a tool to improve students' language skills but also as a rich learning resource with relevant scientific knowledge.